A kind of nano-enhanced powder and its preparation method and application

By adding nano-reinforced powder into traditional foam concrete, the problems of low strength and poor waterproofness of foam concrete are solved, and the preparation of high-performance A05~A07 foam concrete is achieved, which has higher compressive strength, lower water absorption and Better thermal insulation and flame retardant properties.

CN118598577BActive Publication Date: 2025-01-17CHINA RAILWAY CONSTR GRP CONSTR DEV CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411087192.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-01-17
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

The application of traditional foam concrete in load-bearing components is limited by its disadvantages such as low strength, poor waterproofness, unstable thermal conductivity, and prone to cracking.

Method used

Using nano-reinforced powder, the nano-reinforced powder is prepared by mixing nano-viscosity-increasing powder, anti-cracking hardening powder, and large bubble removal and bubble wall hydrophobic powder in a specific proportion, and stirring in a high-speed shear mixer, and Mix it into ordinary cement, control the water-cement ratio within the range of 0.25 to 0.35, and prepare high-performance A05 to A07 foam concrete.

Benefits of technology

It increases the compressive strength of foam concrete by 50-100%, reduces water absorption by 20-30%, has better hydrophobicity, flame retardancy, thermal insulation, sound insulation and non-cracking characteristics, and is suitable for building self-insulating materials. , indoor partition materials and filling materials for road base foundations.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a nano-enhanced powder and a preparation method and application. The nano-enhanced powder is composed of the following raw materials in parts by weight: 60 to 75 parts of nano-thickening powder, 15 to 25 parts of anti-cracking and hardening powder, and 10 to 15 parts of hydrophobic powder for removing large bubbles and bubble walls. Based on the production of traditional foam concrete, the nano-enhanced powder of the present application is added to produce high-performance A05 to A07 foam concrete, with the compressive strength increased by 50 to 100%, and the water absorption rate reduced by 20 to 30%. It has better hydrophobicity, flame retardancy, thermal insulation, sound insulation, no cracking, and light weight, high strength and durability. It is suitable for use in building self-insulating materials for exterior walls, floors and roofs, indoor partition materials, and filling materials for road foundations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a nano-enhanced powder and a preparation method and application thereof. Background Art

[0002] The new generation of foam concrete needs to use new materials with low production energy consumption, good thermal insulation performance, light weight and high strength to replace traditional wall materials, truly promoting the development of energy conservation and building industrialization in my country.

[0003] At present, the application of foam concrete in my country is still mainly in building insulation products, including cast-in-place foam concrete insulation layer of roof, foam concrete blocks, foam concrete lightweight wall panels, foam concrete compensation ground, etc. At present, traditional foam concrete generally has the disadvantage of low strength (for example, dry density 1000kg / m 3 The strength of foamed concrete is usually below 4MPa), which limits its application in load-bearing components. Traditionally used foamed concrete has the disadvantages of low wall material strength, poor waterproofness, unstable thermal conductivity, and easy cracking. The water-cement ratio of ordinary foamed concrete generally needs to be maintained above 0.5, and the internal porosity is as high as more than 40%. The excessively high water-cement ratio causes the foamed concrete to harden. The excess water forms a large number of pores of various pore sizes in the cement stone. During use, micro cracks are generated due to water evaporation and shrinkage of the cement stone structure. The water absorption rate of ordinary foamed concrete is more than 20%. Due to the influence of slurry fluidity, the strength of foamed concrete below grade A11 is often lower than 3.5MPa, which easily leads to water seepage in building walls. The compressive strength of foamed concrete is too low and the durability is extremely poor. Summary of the invention

[0004] In view of the above technical problems in the related art, the present invention provides a nano-enhanced powder and a preparation method and application thereof, which can solve the above problems.

[0005] To achieve the above technical objectives, the technical solution of the present invention is implemented as follows:

[0006] A nano-enhanced powder, which is composed of the following raw materials in parts by weight: 60-75 parts of nano-thickening powder, 15-25 parts of anti-cracking and hardening powder, and 10-15 parts of large bubble and cell wall hydrophobic powder; wherein the nano-thickening powder is a mixture of redispersible latex powder, nano-SiO2 or silicon powder, ultrafine slag powder and vitrified microbead powder in a weight ratio of 0.25-0.5:3.5-5.5:1.0-2.5:1.5-3.5; the anti-cracking and hardening powder is a mixture of fast-hardening sulphoaluminate cement, boric acid and polycarboxylic acid water reducer in a weight ratio of 7.0-8.5:0.5-1.0:1.0-2.5; and the large bubble and cell wall hydrophobic powder is a mixture of polyether defoamer, potassium methyl silicate powder and zinc stearate in a weight ratio of 2.0-3.0:5.0-7.0:1.0-2.0.

[0007] Furthermore, the polycarboxylate water-reducing agent and the polyether defoaming agent are both powders, and the zinc stearate is industrial-grade zinc stearate powder.

[0008] Furthermore, the redispersible rubber powder is a vinyl acetate / ethylene copolymer; the nano-SiO2 is prepared by a gas phase method or a precipitation method; the silicon micropowder is a silicon dioxide micropowder with a content of 96% recovered by an electric furnace; the ultrafine slag powder is S95 grade and has a specific surface area greater than 600m 2 / kg granulated blast furnace slag powder; the vitrified microbead powder is a lightweight hollow silicate powder with a mesh size of 125 or more.

[0009] A method for preparing nano-enhanced powder comprises the following steps: adding the nano-tackifying powder, the anti-cracking and hardening-promoting powder, and the large bubble removing and bubble wall hydrophobic powder into a high-speed shearing mixer in sequence, and rapidly stirring for 5 to 10 minutes to obtain the nano-enhanced powder.

[0010] An application of nano-reinforced powder, wherein the nano-reinforced powder is applied to foamed concrete.

[0011] Furthermore, M parts by weight of the nano-reinforced powder are added to every N parts by weight of ordinary cement to obtain a cementitious material containing the nano-reinforced powder, and the water-cement ratio is controlled within the range of 0.25 to 0.35 to obtain a hardened slurry, wherein N+M=100, and 25≤M≤50.

[0012] Furthermore, a foam machine is used to prepare aqueous animal protein foam on site.

[0013] Furthermore, prefabricated aqueous animal protein foam is added according to 10% to 15% of the total mass of the hardened slurry to obtain foamed concrete.

[0014] Furthermore, the foamed concrete is A05-A07 foamed concrete.

[0015] The beneficial effects of the present invention are as follows: on the basis of traditional foam concrete production, by adding the nano-enhanced powder of the present application, high-performance A05-A07 foam concrete can be made, the compressive strength is increased by 50-100%, the water absorption rate is reduced by 20-30%, and it has better water repellency, flame retardancy, thermal insulation, sound insulation, no cracking, light weight, high strength and durability, etc. It is suitable for use in building self-insulating materials for exterior walls, floors and roofs, indoor partition materials, and filling materials for road foundations. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0017] The invention discloses a nano-enhanced powder, a preparation method and an application thereof. The nano-enhanced powder is composed of the following raw materials in parts by weight: 60 to 75 parts of nano-tackifying powder, 15 to 25 parts of anti-cracking and hardening-promoting powder, and 10 to 15 parts of hydrophobic powder for removing large bubbles and bubble walls.

[0018] The nano-thickening powder is a mixture of redispersible latex powder (VAE), nano-SiO2 or silica powder, ultrafine slag powder (KZ) and vitrified microbead powder (WZ) in a weight ratio of 0.25-0.5:3.5-5.5:1.0-2.5:1.5-3.5. The purpose is to improve the internal strength and viscosity of the slurry structure. The redispersible rubber powder is vinyl acetate / ethylene copolymer, or other acrylic copolymers; the nano-silicon dioxide is nano-silicon dioxide prepared by gas phase method or precipitation method, and the silica powder is 96% silica powder recovered from an electric furnace; the ultrafine slag powder is S95 grade and has a specific surface area greater than 600m 2 / kg granulated blast furnace slag powder; vitrified microsphere powder is a lightweight hollow silicate powder with a mesh size of 125 or above. The nano-thickening powder can enhance the foam concrete matrix and foam wall. The effect is verified by testing the GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)" standard to test the compressive strength of high-strength slurry at 7d and 28d.

[0019] The anti-cracking and hardening powder is a mixture of fast-hardening sulphoaluminate cement (SAC) with micro-expansion anti-cracking and hardening performance, boric acid (H3BO3) with special slow-setting performance, and polycarboxylate water-reducing agent (PCE) that reduces the amount of water in the slurry and improves the fluidity and hardening strength of the slurry, with a weight ratio of 7.0-8.5:0.5-1.0:1.0-2.5. The purpose is to ensure the rapid formation of the foam concrete support structure to achieve the effect of strengthening without cracking. The effect can be verified by testing the mortar test block or the drying shrinkage rate of the foam concrete.

[0020] The large bubble and cell wall hydrophobic powder is a mixture of polyether defoamer (PE), methyl potassium silicate powder (MPS), and zinc stearate (Zins stearas, simplified Zins) in a weight ratio of 2.0-3.0:5.0-7.0:1.0-2.0. The purpose is to eliminate large bubbles, increase the number of uniform microbubbles, make the hardened foam concrete products waterproof and impermeable, reduce the water absorption rate of foamed soil, ensure the thermal insulation effect, and high durability with the same life as the main structure of the building. The effect verification can detect the water absorption rate, thermal conductivity and other related performance indicators of the foamed concrete.

[0021] When preparing nano-enhanced powder, the nano-tackifying powder, the anti-cracking and hardening powder, and the large bubble removing and cell wall hydrophobic powder are sequentially added into a high-speed shearing mixer and rapidly stirred for 5 to 10 minutes to obtain the nano-enhanced powder.

[0022] When the nano-enhanced powder is applied to foamed concrete, M parts by weight of the nano-enhanced powder is added to every N parts by weight of ordinary cement to obtain a cementitious material containing the nano-enhanced powder, and the water-cement ratio is controlled within the range of 0.25 to 0.35 to obtain a hardened slurry, wherein N+M=100, and 25≤M≤50 (a high-strength and high-performance hardened slurry for foamed concrete with a 28-day strength of 45.0 to 65.0 MPa can be obtained), and a water-based animal protein foam is prepared on-site using a foam machine, and the foam quality meets the requirements of JC / T2199-2013 "Foaming Agent for Foamed Concrete" The performance indicators of the foaming agent are tested by the method, and prefabricated aqueous animal protein foam is added according to 10% to 15% of the total mass of the hardened slurry to obtain foamed concrete. The foamed concrete is high-strength and high-performance A05-A07 foamed concrete. The high-strength and high-performance A05-A07 foamed concrete mixed with nano-reinforced powder has a 7-day and 28-day hardening compressive strength that can be increased by 50-100% compared with foamed concrete without nano-reinforced powder. The concrete has the characteristics of light weight, water repellency, no cracking, flame retardancy, thermal insulation, sound insulation, etc. It has the same lifespan as the main structure of the building and is more widely used.

[0023] Several nano-enhanced powders with different proportions were prepared by the above-mentioned nano-enhanced powder preparation method, as shown in Table 1 for details.

[0024] Table 1 Nano-enhanced powder proportions for foamed concrete

[0025] ;

[0026] The nano-enhanced powder for foamed concrete is used in A05-A07 foamed concrete, as shown in Examples 7-18 and Comparative Examples 1-3 of A05, A06 and A07, as shown in Tables 2-4. The performance tests are carried out according to the Technical Specification for Application of Foamed Concrete JGJ / T 341-2014 and JG / T 266-2011 Foamed Concrete, GB / T 10294-2008 Determination of Steady-State Thermal Resistance and Related Properties of Insulating Materials - Protected Hot Plate Method and other standards.

[0027] Table 2 A05 grade foam concrete unit dosage and test results

[0028] ;

[0029] Table 3 A06 grade foam concrete unit dosage and test results

[0030] ;

[0031] Table 4 A07 grade foam concrete unit dosage and test results

[0032] ;

[0033] The mix design of foam concrete in actual engineering applications is based on the principle of meeting density, compressive strength, workability and thermal insulation performance. The surplus coefficient of various materials in the slurry is 1.1 to 1.3. The foaming agent is animal protein, with a foaming multiple of about 25, 1:30 water foaming, and a foam density of about 110Kg / M 3 To prepare foamed concrete, the slurry should be injected into the mixing drum of the mixer first, and then the foam should be injected. The slurry and foam should be mixed and stirred for 3min to 5min. When the color of the foamed concrete slurry is uniform and the individual white spots on its surface no longer change significantly, the stirring can be stopped to make a uniform fluid slurry of high-strength foamed concrete. During the performance test, the casting size of the compression test piece is 100mm×100mm×100mm, and the size of the thermal conductivity standby test piece is 300mm×300mm×300mm. The curing environment is room temperature 25℃±3℃, and the room temperature is placed for 8 to 12 hours before demolding. The test block is sprayed with water once a day and cured to the specified age. The compression test block is placed in an 85℃ drying oven to constant weight, and the dry density, water absorption and strength are measured.

[0034] In summary, the present invention is based on the traditional foam concrete production, and the nano-enhanced powder is added to make the high-performance A05-A07 foam concrete. At 28 days, the compressive strength can be increased to 4.5-11.0MPa, which is actually increased by 50-100%. It has water repellency, flame retardancy, crack resistance, heat insulation, sound insulation and excellent durability. It solves the technical problems of low strength, poor water resistance, large thermal conductivity and easy cracking that are common in the existing foam concrete. It breaks through the bottleneck of foam concrete development-solving the problem of low compressive strength and excessive water absorption of foam concrete wall materials, and systematically solves the application problems such as poor fluidity during concrete mixing and foaming and easy cracking after molding. It truly realizes the self-insulation of the building wall enclosure structure, the wall does not crack or seep water, and can have the same lifespan as the main structure of the building. It is suitable for building self-insulating wall materials for exterior walls, floors and roofs, indoor partition materials, and filling materials for road foundations.

[0035] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A nano-enhanced powder, characterized in that: The nano-enhanced powder is composed of the following raw materials in parts by weight: 60-75 parts of nano-thickening powder, 15-25 parts of anti-cracking and hardening powder, and 10-15 parts of large bubble and cell wall hydrophobic powder; wherein the nano-thickening powder is a mixture of redispersible latex powder, nano-SiO2 or silicon powder, ultrafine slag powder and vitrified microbead powder in a weight ratio of 0.25-0.5:3.5-5.5:1.0-2.5:1.5-3.5; the anti-cracking and hardening powder is a mixture of fast-hardening sulphoaluminate cement, boric acid and polycarboxylic acid water reducer in a weight ratio of 7.0-8.5:0.5-1.0:1.0-2.5; the large bubble and cell wall hydrophobic powder is a mixture of polyether defoamer, potassium methyl silicate powder and zinc stearate in a weight ratio of 2.0-3.0:5.0-7.0:1.0-2.

0.

2. A nano-enhanced powder according to claim 1, characterized in that: The polycarboxylate water reducer and the polyether defoamer are both powders, and the zinc stearate is industrial grade zinc stearate powder.

3. A nano-enhanced powder according to claim 1, characterized in that: The redispersible rubber powder is a vinyl acetate / ethylene copolymer; the nano-SiO2 is prepared by a gas phase method or a precipitation method; the silicon micropowder is a silicon dioxide micropowder with a content of 96% recovered by an electric furnace; the ultrafine slag powder is S95 grade and has a specific surface area greater than 600m 2 / kg granulated blast furnace slag powder; the vitrified microbead powder is a lightweight hollow silicate powder with a mesh size of 125 or more.

4. A method for preparing the nano-enhanced powder according to any one of claims 1 to 3, characterized in that: The nano-thickening powder, the anti-cracking and hardening powder, and the large bubble removing and cell wall hydrophobic powder are sequentially added into a high-speed shearing mixer and rapidly stirred for 5 to 10 minutes to obtain the nano-enhanced powder.

5. An application of the nano-enhanced powder according to any one of claims 1 to 3, characterized in that: The nano-enhanced powder is applied to foamed concrete.

6. The use of the nano-enhanced powder according to claim 5, characterized in that: M parts by weight of the nano-enhanced powder are added to every N parts by weight of ordinary cement to obtain a cementitious material containing the nano-enhanced powder, and the water-cement ratio is controlled within the range of 0.25 to 0.35 to obtain a hardened slurry, wherein N+M=100, and 25≤M≤50.

7. The use of the nano-enhanced powder according to claim 6, characterized in that: Aqueous animal protein foam is prepared on-site using a foam machine.

8. The use of the nano-enhanced powder according to claim 7, characterized in that: Prefabricated aqueous animal protein foam is added according to 10% to 15% of the total mass of the hardened slurry to obtain foamed concrete.

9. The use of the nano-enhanced powder according to claim 8, characterized in that: The foamed concrete is A05-A07 foamed concrete.

Citation Information

Patent Citations

  • Building insulating mortar containing nano-silica aerogel

    CN102424538A

  • Flyash foam thermal insulation board

    CN2460617Y